Pembelajaran Daring di Masa Pandemi Covid-19 (Current Research in Education: Conference Series Journal, 2022)
The purpose of this scientific article is to analyze the education challenge currently facing Indonesia, namely the application of online learning methods during the Covid-19 pandemic. During the Covid-19 pandemic, almost all schools and universities in Indonesia implemented online or online learning. Online learning is an innovation in education where learning uses information technology in the form of assistance using an internet network with accessibility, connectivity, flexibility, and the ability to generate various learning interactions and use electronic tools to be able to access learning using the internet, namely using cellphones, laptops and others . The method used in this research is literature study and quantitative methods carried out by survey using Google Form, the results of the study have a positive impact that occurs in online learning, based on the conclusion of the survey results of respondents, namely that many think that this online learning can minimize and reduce the rate. the spread of the Covid 19 disease because this learning is mostly done at home, then the negative impact of the lack of understanding of the material delivered by the teacher or lecturer, and feeling that online learning is less effective because they do not understand the material presented by their teacher or lecturer and the wasteful use of quotas